Report on the lessons learned on developing NAMAs from a policy perspective taking into account productive experiences of sustainable livestock in Colombia - Tapasco, Jeimar; Le Coq, Jean-François; Ruden, Alejandro; Rivas, Juan Sebastián; Ortíz, Javier (2019)
Livestock plays an important role in the Colombian economy, however, it is responsible for a high percentage of GHGs emitted into the atmosphere. For this reason, the objective of this work was to know the existing initiatives in sustainable livestock that allow generating models to implement technologies and improve livestock systems in the productive area and the environmental scope, which includes the mitigation of greenhouse gases and conservation of ecosystems.